2012
DOI: 10.2310/jim.0b013e31823581dd
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress, the Activities of Paraoxonase and Arylesterase in Patients with Subclinical Hypothyroidism

Abstract: The activity of PON and ARE were significantly decreased, and oxidative stress was increased in patients with SH. Lower activities of these 2 biomarkers indicate increased oxidative damage in SH. Atherosclerosis in SH can be attributed to increased oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
5
47
0
Order By: Relevance
“…Similarly, Cebeci et al (30) revealed in their study that PON and arylesterase levels were lower in patients with subclinical hypothyroidism when compared to the healthy control group. Similar to the above studies, we have also found lower arylesterase and log(PON1) levels in patients with subclinical and overt hypothyroidism than in the healthy controls.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Similarly, Cebeci et al (30) revealed in their study that PON and arylesterase levels were lower in patients with subclinical hypothyroidism when compared to the healthy control group. Similar to the above studies, we have also found lower arylesterase and log(PON1) levels in patients with subclinical and overt hypothyroidism than in the healthy controls.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Indices of oxidative stress were found to be increased [7,[9][10][11][12][13], decreased [8] or unchanged [14] in hypothyroid state. Meanwhile, there is little and controversial knowledge about oxidative stress in subclinical hypothyroidism defined as the presence of high levels of thyroid stimulating hormone (TSH) and normal values of free triiodothyronine (fT 3 ) and free thyroxine (fT 4 ) [9,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported increased OS in adult patients with SHT [11-13]; these studies either included only patients with autoimmune hypothyroidism [11-13] or the presence of autoimmune thyroiditis was not reported [20, 21]. Hashimoto thyroiditis is a chronic inflammatory auto­immune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thiol/disulphide homeostasis is regarded as an indicator of OS [9, 10]. OS markers have been found to be increased in patients with autoimmune SHT [11-13]. …”
Section: Introductionmentioning
confidence: 99%